2015
DOI: 10.1016/j.jacc.2014.11.031
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of a Dedicated Bifurcation Stent Versus Provisional Stenting in the Treatment of Coronary Bifurcation Lesions

Abstract: Provisional stenting should remain the preferred strategy for treatment of non-left main true coronary bifurcation lesions. (Prospective, Single Blind, Randomized Controlled Study to Evaluate the Safety & Effectiveness of the Tryton Side Branch Stent Used With DES in Treatment of de Novo Bifurcation Lesions in the Main Branch & Side Branch in Native Coronaries [TRYTON]; NCT01258972).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 35 publications
3
92
0
Order By: Relevance
“…624,625 Several stents, designed specifically for the treatment of bifurcation lesions, have undergone extensive evaluation with promising angiographic and clinical results, though RCTs against current recommended therapy are limited. 626 Further technical details relating to bifurcation PCI are described in the consensus document of the European Bifurcation Club. 627 …”
Section: Bifurcation Stenosismentioning
confidence: 99%
“…624,625 Several stents, designed specifically for the treatment of bifurcation lesions, have undergone extensive evaluation with promising angiographic and clinical results, though RCTs against current recommended therapy are limited. 626 Further technical details relating to bifurcation PCI are described in the consensus document of the European Bifurcation Club. 627 …”
Section: Bifurcation Stenosismentioning
confidence: 99%
“…[19] However, provisional bifurcation side branch treatment guided by FFR provided no benefit compared to angiography guided provisional treatment [20]. A recent randomized trial showed there was no benefit of a dedicated bifurcation stent compared to traditional, provisional stenting of the side branch [21].…”
Section: Discussionmentioning
confidence: 99%
“…Probably the greatest drawback is the limited range of lengths of the devices, which most frequently results in additional stent(s) implantation, increasing the cost of the procedure. The SB-dedicated stenting with Tryton stent (not the drug-eluting version) did not reach its primary non-inferiority end-point in comparison with regular DES [51]. It demonstrated such non-inferiority only in the group with SB reference diameter more than 2.25 mm.…”
Section: General Conclusion and Future Directionsmentioning
confidence: 85%